If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 5) = (3x + -1) Reorder the terms: (5 + x) = (3x + -1) Remove parenthesis around (5 + x) 5 + x = (3x + -1) Reorder the terms: 5 + x = (-1 + 3x) Remove parenthesis around (-1 + 3x) 5 + x = -1 + 3x Solving 5 + x = -1 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 5 + x + -3x = -1 + 3x + -3x Combine like terms: x + -3x = -2x 5 + -2x = -1 + 3x + -3x Combine like terms: 3x + -3x = 0 5 + -2x = -1 + 0 5 + -2x = -1 Add '-5' to each side of the equation. 5 + -5 + -2x = -1 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = -1 + -5 -2x = -1 + -5 Combine like terms: -1 + -5 = -6 -2x = -6 Divide each side by '-2'. x = 3 Simplifying x = 3
| -0.3-2.7=-4.1 | | B+8=2 | | 5(r+3)=4+2r+2 | | x-2.3=6.4 | | 750=y+(y*.07) | | 15-3x=7x+5 | | 6cos-1=2 | | 4(q)=52 | | 2(4x+1)=3x-9x | | 1996.43x=7385-67x | | R-(-5)=9 | | 8(4-n)+2=90 | | 44221=a*2+b | | 2(5x+7)+3=10x+17 | | 2x-17=2x-12 | | 3(r+7)=15 | | 4r-1=-4+4r+3 | | -4(x+9)=7-3x | | 2(4x-10)=46 | | 3m+3=5 | | -15+3=-2(x+7) | | 1996+43x=3716 | | 3x+3=(x+3) | | 10(a-2)=-70 | | -86=-7n+4(-n-5) | | 7-3x-5-3x=5 | | Kx-3x=-2+5k | | 360-76= | | -8-14v=314 | | 5(-x-3)=5 | | 16x+34x+24x=370 | | 9(n+12)=144 |